SAR (Synthetic Aperture Radar) Image Study and Analysis for Object Recognition in Surveillance - Pawar , Sushant J.; Gandhe, Sanjay. T. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
A summary of the many techniques used for this comprehensive review study aims to classify and detect synthetic aperture radar (SAR) images. SAR images have become more well-liked as a result of their adaptability and use in remote sensing activities such as planning, surveillance, and search and rescue regardless of the weather. The conversion of radar scatter returns to images and subsequent analysis for composition determination make it difficult to interpret these images efficiently. SAR images have been effectively categorized in the past for a variety of uses, with the possibility for further expansion across other SAR image types. In particular, feature extraction and SAR image categorization using Convolutional Neural Networks (CNNs) show potential.